Propolis Mitigates Rifampicin/Isoniazid-induced Lipid-redox and Metabolic Profile in an Experimental Animal Model of Oxidative Stress - Abdulsallam, Ahmed; Thanoon, Imad A.; Dawood, Rwqaya S.; Abduljabbar, Abdulrahman I. (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective: Adverse drug reactions are the most common cause of drug withdrawal in chronic treatment settings. Tuberculosis (TB) has been considered a recurrent and relapsing disease that needs long-term therapy. Most patients suffer from the adverse effects of TB therapy. Hence, various remedies were used to tackle these adverse effects including antioxidant vitamins, herbal remedies, and others. Aims: The present intervention study aims to investigate the role of propolis in protecting the animal model against oxidant/antioxidant induced by TB therapy together with the propolis role in modulation of metabolic profile as part of lipid peroxidation context. Methods: Serum was collected from rats exposed to rifampicin/isoniazid with or without propolis therapy alongside the control placebo group for comparison. Results: The results have shown a significant (p<0.05) reduction of malondialdehyde and significant (p<0.05) elevation of total antioxidant status. Lipid profile positively improved indicated by significantly reduced total cholesterol, triglyceride, and elevated high-density lipoprotein. Conclusion: our study confirmed that propolis provides protection against redox and metabolic derangement induced by rifampicin/isoniazid medications which are in current TB therapy, therefore, we do advise the use of propolis as an adjunct therapy for patients on such medications.